Revision of Afro-Malagasy Otomops (Chiroptera: Molossidae) with the description of a new Afro-Arabian species - Ralph, Taryn M. C.; Richards, Leigh R.; Taylor, Peter J.; Napier, Melanie C.; Lamb, Jennifer M. (Zootaxa, 2015)
The paucity of data for the molossid bat Otomops throughout its range has hindered our ability to resolve the number of Otomops species present within the Afro-Malagasy region (including the Arabian Peninsula). This paper employed an integrative approach by combining morphometric (cranial morphology) and molecular (mitochondrial cytochrome b and D-loop sequences, nuclear intron sequences and microsatellites) data to identify the number of Otomops taxa occurring in the Afro-Malagasy region. Three taxa were identified, two of which could be assigned to existing species, i.e. O. martiensseni and O. madagascariensis. The third taxon, previously recognised as O. martiensseni (Matschie 1897), is described herein as a new species, Otomops harrisoni sp. nov., and can be differentiated from O. martiensseni s.s. based on both molecular and morphometric data. Locality data of specimens belonging to O. harrisoni suggest that its distribution range extends from the Arabian Peninsula through to Eritrea and south to Ethiopia and Kenya.